Bronchoalveolar lavage cell percentages as diagnostic markers of immune checkpoint inhibitor pneumonitis - Mahnoor Mir; Felipe Soto; Pedro Antonio Amezcua Gomez; Rodrigo Del Rio Arroyo; Adarsh Suresh; Amber Su; Qiong Gan; John Stewart; Roberto Adachi; Diwakar D. Balachandran; Lara Bashoura; Roberto F. Casal; et al. (Frontiers in Medicine, 2025)
IntroductionDiagnostic biomarkers for immune checkpoint inhibitor pneumonitis (ICIP) are lacking. Bronchoalveolar lavage (BAL) lymphocytosis has been associated with ICIP, but studies have not evaluated BAL lymphocytosis as a diagnostic biomarker for ICIP.PurposeThis study aimed to measure the association of BAL immune cell percentage with ICIP and test its performance as a diagnostic biomarker.MethodsWe performed a retrospective chart review of 476 patients treated with ICIs for solid organ or hematologic malignancies who underwent BAL between 2016 and 2022. Two independent reviewers, blinded to the results of BAL cell percentage, confirmed the diagnosis of ICIP or other conditions (e.g., pneumonia) based on clinical history and radiology. We constructed logistic regression models to assess the relationship between BAL lymphocyte, eosinophil, and neutrophil percentages and the diagnosis of pneumonitis, and the area under the receiver-operator curves (AUROC) was used to assess their discriminatory function. We measured the association of BAL immune cell percentages with 1-year overall survival using Cox proportional hazard models adjusted for age and cancer diagnosis.ResultsEach 1% increase in lymphocyte (OR 1.01, 95% CI 1.01–1.02, p < 0.001) and eosinophil percentage (OR 1.05, 95% CI 1.01–1.11, p = 0.01) were independently associated with pneumonitis, while neutrophil percentage was inversely associated (OR 0.99, 95% CI 0.98–0.99, p = 0.01) with pneumonitis. In multivariable analysis, lymphocyte percentage (OR 1.02, 95% CI 1.009–1.04, p = 0.002) and eosinophil percentage (OR 1.10, 95% CI 1.01–1.23, p = 0.05) were both associated with ICIP. The AUROC for BAL lymphocytes to diagnose ICIP was 0.62 (95% CI 0.57–0.67, optimal cutoff 15.5%, sensitivity 69%, and specificity 52%) and the AUROC for eosinophils was 0.61 (95% CI 0.56–0.66, optimal cutoff 1%, sensitivity 58%, and specificity 62%). In patients with pneumonitis, lymphocyte percentage (HR 0.99, 95% CI 0.97–1.00, p = 0.02), neutrophil percentage (HR 1.01, 95% CI 1.00–1.02, p = 0.05), and eosinophil percentage (HR 0.93, 95% CI 0.86–0.99, p = 0.03) were associated with 1-year survival.ConclusionBAL lymphocytosis and eosinophilia are associated with ICIP, but their ability to discriminate ICIP from other conditions is modest. BAL immune cell percentages may have prognostic value for 1-year survival, but this likely reflects the morbidity of other pulmonary diseases that require BAL for evaluation.